The Influence of Parenting Patterns on the Independence of 5-6 Year Old Children at Alzepa PAUD, Kandis Village, Pampang District - Yecha Febrienitha Putri; Riski Lestari; Febriyanti; Leny Marlina; Elsa Cindrya (Universitas PGRI Madiun, 2026)
Low independence abilities of children aged 5-6 years. The research aims to determine the influence of parenting styles on the independence of children aged 5-6 years at PAUD Alzepa. The research design is quantitative and ex post facto. The study sample consisted of 13 children. The information was collected from respondents using observation, questionnaires, and documentation. The analysis techniques used in the research are the normality test, the simple linear regression test, and hypothesis testing. Based on research conducted, parental parenting patterns significantly influence the independence of children aged 5-6 years. The correlation value between x and y is 0.785, which is in the strong category. The coefficient of determination value is 0.664 or 66.4%. This means that x can influence y by 66.4%; the rest is influenced by other factors. regression equation y=4.41+1.34, which means if x is 1, then y is 4.41. The value of x is 1.34 between variables x and y; when x increases by 1, y increases by 1.34. F-calculated significance value is 0.005<alpha=0.05, so it can be concluded that there is an influence of variable X on variable Y.